The Context and Challenges of Interdisciplinarity in the Philippines - Cuyegkeng, Maria Assunta C. (Archīum Ateneo, 2024)
The tension between disciplines and interdisciplinary initiatives has been present in different areas around the world. This paper discusses the roots of the tension in the world and in the Philippines, as well as issues and challenges of implementation. It begins with the meaning of discipline and the nuances in the interaction of multiple disciplines, (e.g. multidisciplinary, interdisciplinary, or transdisciplinary) and traces and traces the development of disciplines in relation to the development of higher education. While academic departments and programs give life and power to the disciplines, there were pressures to work across disciplines to achieve the underlying goals of scholarship. Multiple disciplines are needed in solving real-world problems, understanding complex systems, implementing policy or applying research, and generating groundbreaking ideas. However, there are challenges in implementing interdisciplinarity in the Philippines and this includes issues tied up with the implementation process; the need for leadership to navigate through the complex relationships of the disciplines; the balance of grounding in the discipline and interdisciplinarity; assessment of outcomes of interdisciplinary work; and defining an institution’s desired outcomes to guide the support systems.